Activation of AMPK/miR-181b Axis Alleviates Endothelial Dysfunction and Vascular Inflammation in Diabetic Mice - Chak-Kwong Cheng; Wenbin Shang; Jian Liu; Wai-San Cheang; Yu Wang; Li Xiang; Chi-Wai Lau; Jiang-Yun Luo; Chi-Fai Ng; Yu Huang; Li Wang (MDPI AG, 2022)
Hyperglycemia in diabetes mellitus impairs endothelial function and disrupts microRNA (miRNA) profiles in vasculature, increasing the risk of diabetes-associated complications, including coronary artery disease, diabetic retinopathy, and diabetic nephropathy. miR-181b was previously reported to be an anti-inflammatory mediator in vasculature against atherosclerosis. The current study aimed to investigate whether miR-181b ameliorates diabetes-associated endothelial dysfunction, and to identify potential molecular mechanisms and upstream inducer of miR-181b. We found that miR-181b level was decreased in renal arteries of diabetic patients and in advanced glycation end products (AGEs)-treated renal arteries of non-diabetic patients. Transfection of miR-181b mimics improved endothelium-dependent vasodilation in aortas of high fat diet (HFD)/streptozotocin (STZ)-induced diabetic mice, accompanied by suppression of superoxide overproduction and vascular inflammation markers. AMPK activator-induced AMPK activation upregulated miR-181b level in human umbilical vein endothelial cells (HUVECs). Chronic exercise, potentially through increased blood flow, activated AMPK/miR-181b axis in aortas of diabetic mice. Exposure to laminar shear stress upregulated miR-181b expression in HUVECs. Overall, our findings highlight a critical role of AMPK/miR-181b axis and extend the benefits of chronic exercise in counteracting diabetes-associated endothelial dysfunction.